The Russian Empire, Slaving and Liberation, 1480-1725 Trans-Cultural Worldviews in Eurasia - Witzenrath, Christoph (Dependency and Slavery Studies, 2022)
The monograph realigns political culture and countermeasures against slave raids, which rose during the breakup of the Golden Horde. By physical defense of the open steppe border and embracing the New Israel symbolism (exodus from slavery in Egypt/among the Tatars), Muscovites found a defensive model to expand the empire. Recent debates on slaving are introduced to Russian and imperial history, while challenging entrenched perceptions of Muscovy.